Hip hop v Sloveniji: ali obstaja lokalno specifičen vzorec prevzemanja značilnosti žanra? - Stanković, Peter (Družboslovne razprave, 2006)
A strong local hip hop scene has been present in Slovenia for some time now, yet it is unclear whether Slovenian hip hop is merely a copy of a globally established musical genre or in fact an innovative hybrid established at the intersection of global trends and their local cultural variations. To address this question, the author examines ten of the most important Slovenian hip hop MCs/groups, arguing that while Slovenian hip hop does not show many local cultural peculiarities the appropriations of this global genre are nevertheless remarkably uniform: of all elements of the genre, Slovenian hip hop musicians above all combine hip hop music with distinctively critical lyrics. This pattern is, of course, not remarkable as such but it may signal the beginning of new hybrid form or, as it is, the fact that hip hop in Slovenia functions primarily as a medium of construction of the typically critical one could even say of modernist subjectivity.
Keywords: Popular music; Popularna glasba; Popularna kultura; Popular culture; Slovenia; Slovenija; mladina; hip hop